A top-down approach making cellulose carbonaceous aerogel/MnO2 ultrathick bulk electrodes with high mass loading for supercapacitors. (30th September 2021) - Zhang, Weiye; Li, Yanchen; Wang, Beibei; Sun, Jingmeng; Lin, Lin; Liu, Yi; Guo, Hongwu
Abstract : A cellulose carbonaceous aerogel/MnO2  ultrathick electrode with a unique low curvature, porous carbon thin-walled tube array structure was obtained from natural wood using a simple top-down approach. Abstract : A thick electrode design can improve the specific capacitance of an electrode by increasing the volume ratio of the active to inactive materials. However, if the thickness is too large, the transmission of electrons and ions along the thickness direction becomes difficult, leading to a decrease in specific capacitance. Herein, inspired by the high-flux water transfer channels of trees, the unique microstructure can transport electrons and ions rapidly in a supercapacitor electrode. A simple top-down approach was used to remove lignin and hemicellulose from natural wood. Subsequent carbonization resulted in a cellulose carbonaceous aerogel (CCA) with a unique low curvature, porous carbon thin-walled tube array structure. Due to the unique structure of the CCA, the ultrathick electrode (a thickness up to 1500 μm) could achieve a high MnO2 mass loading value of 91.0 wt%. The prepared electrode has an excellent areal specific capacitance (3982 mF cm −2 at 1.0 mA cm −2 ), a long cycle life (82.4% retention after 5000 cycles) and low deformation. The proposed thick electrode design concept will open a new avenue to enhance the capacitance performance of supercapacitors.